Long Term Trends in Climate Variability of Caucasus Region - Nurtaev, Bakhram S.; Nurtaev, Lali (Journals of Georgian Geophysical Society, 2017)
Over the period 1855–1996 was observed a long-term increase trend of solar activity, that leads to temperature rise. In the Caucasus region it is also observed a warming trend.The main goal of this study is to identify contribution of the Sun on climate variability of Caucasus Mountains and long term prediction of future climate trend in the region for sustainable development.